Ambulatory pediatric oncology CLABSIs: Epidemiology and risk factors. Issue 11 (23rd July 2013) - Rinke, Michael L.; Milstone, Aaron M.; Chen, Allen R.; Mirski, Kara; Bundy, David G.; Colantuoni, Elizabeth; Pehar, Miriana; Herpst, Cynthia; Miller, Marlene R.
Abstract Background To compare the burden of central line‐associated bloodstream infections (CLABSIs) in ambulatory versus inpatient pediatric oncology patients, and identify the epidemiology of and risk factors associated with ambulatory CLABSIs. Procedure We prospectively identified infections and retrospectively identified central line days and characteristics associated with CLABSIs from January 2009 to October 2010. A nested case–control design was used to identify characteristics associated with ambulatory CLABSIs. Results We identified 319 patients with central lines. There were 55 ambulatory CLABSIs during 84, 705 ambulatory central line days (0.65 CLABSIs per 1, 000 central line days (95% CI 0.49, 0.85)), and 19 inpatient CLABSIs during 8, 682 inpatient central line days (2.2 CLABSIs per 1, 000 central lines days (95% CI 1.3, 3.4)). In patients with ambulatory CLABSIs, 13% were admitted to an intensive care unit and 44% had their central lines removed due to the CLABSI. A secondary analysis with a sub‐cohort, suggested children with tunneled, externalized catheters had a greater risk of ambulatory CLABSI than those with totally implantable devices (IRR 20.6, P < 0.001). Other characteristics independently associated with ambulatory CLABSIs included bone marrow transplantation within 100 days (OR 16, 95% CI 1.1, 264), previous bacteremia in any central line (OR 10, 95% CI 2.5, 43) and less than 1 month from central line insertion (OR 4.2, 95% CI 1.0, 17). Conclusions In pediatric oncology patients, three times more CLABSIs occur in the ambulatory than inpatient setting. Ambulatory CLABSIs carry appreciable morbidity and have identifiable, associated factors that should be addressed in future ambulatory CLABSI prevention efforts. Pediatr Blood Cancer 2013;60:1882–1889. © 2013 Wiley Periodicals, Inc.